Epidendrum machinense (Orchidaceae: Laeliinae), a new species from Colombia - Rincón-González, Milton; Escalante, María Fernanda (Phytotaxa, 2020)
A new species of Epidendrum from central Andes of Colombia is described and illustrated. Epidendrum machinense belongs to the Mancum group, Stenoglossum subgroup; being only the third species known to belong to that subgroup. The new species is characterized by having larger plants with respect to its close relatives, bearing 50–80 flowers per inflorescence, the flowers are resupinate due to drooping of the rachis, rather than the twisting of the pedicel; the petals are 3–veined, yellow tinged purple-brown, with completely yellow apices, the lip is white with numerous wine-red spots, 3–lobed, with broadly hamate lateral lobes, and a mid-lobe with a rombic or bifid apex. Information on the species distribution, habitat and phenology, conservation status, and characters that distinguish it from the nearest species are provided, as well as an annotation on resupination in the Stenoglossum subgroup.